Screening for hepatocellular carcinoma in chronic liver disease: a systematic review and meta-analysis of randomized controlled trials comparing screening methodologies - James O'Connell; Siobhan Rooney (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Globally, hepatocellular carcinoma (HCC) is the fifth most prevalent cancer and the second most common cause of cancer-related mortality. HCC is often asymptomatic until an advanced stage. Current guidelines recommend ultrasound surveillance with or without measurement of serum alpha-fetoprotein. Our objective was to determine if screening for HCC is beneficial or harmful in patients with chronic liver disease. Primary outcomes were all-cause mortality and quality of life. Secondary outcomes were mortality due to HCC, the number of cases of HCC detected, and adverse events. # Methods This is a systematic review and meta-analysis of data from randomized controlled trials. To be included trials had to randomize patients to either an HCC screening group or non-screening group, randomize patients to different screening frequencies or randomize patients to different screening methods. All published reports of randomized trials on screening for HCC were eligible for inclusion, irrespective of the language of publication. Studies had to include patients with chronic liver disease. Data extraction were performed independently by two reviewers. # Results When screening with six-monthly alpha-fetoprotein and ultrasound abdomen was compared to no screening there was no evidence of difference in HCC related mortality when adjusted for clustering across a range of intracluster correlation coefficients (Intracluster coefficient (ICC) 0.02, odds ratio (OR) 0.60, 95% confidence interval (CI) 0.31-1.15). Screening with six-monthly alpha-fetoprotein when compared to a single alpha-fetoprotein check did not result in a statistically significant difference in all-cause mortality (OR 1.02, 95% confidence interval (CI) 0.65-1.60), mortality due to HCC (OR 1.01, 95% CI 0.57-1.78) or the number of HCC detected (OR 1.11 95% CI 0.64-1.92). There was no evidence of difference in all-cause mortality (OR 0.81, 95% CI 0.26-2.53), mortality due to hepatocellular carcinoma (OR 0.81, 95% CI 0.26-2.53) or the number of patients with HCC detected (OR 1.09 95% CI 0.40-2.99) when twice-a-year ultrasound was compared with annual CT. There was no statistically significant difference when screening more frequently was compared to less frequently in terms of all-cause mortality (OR 0.86, 95% CI 0.56-1.32), mortality due to hepatocellular carcinoma (OR 1.42, 95% CI 0.55-3.64) and the number of cases of hepatocellular carcinoma detected (OR 0.90 95% CI 0.47-1.71). # Conclusion There is currently insufficient evidence from randomized controlled trials to support routine screening for HCC in patients with chronic liver disease.